Counselling Difficult Children - Ritchie, Martin H. (Canadian Journal of Counselling and Psychotherapy, 2007)
Unique aspects of counselling difficult children (ages 4-12) are examined. Because most children are involuntarily referred, counsellors must expect resistance and accept it as a reasonable reaction. Counsellors engage children by explaining the rules of counselling and gaining informed consent. Methods for securing a commitment to change include: indirect confrontation with puppets, media or stories; paradox and reframing; modelling and role plays. Because children have little control over their environment, it is suggested that therapeutic change be facilitated and maintained by enlisting the aid of significant others.